Improving mechanical grip on winter tires. Finite element analysis on pressure profile of airless tire compared to conventional tire using ANSYS workbench - Ludvigsen, Sondre (UiT The Arctic University of Norway, 2017)
The harsh climate of the arctic has always been one of the most difficult areas to drive cars in. The severe loss in traction due to snow and icing on the roads, has led to an increased risk of collisions. The winter tires for cars has developed through the years after their introduction in the 1930’s. There have been three revolutionary changes made since then; implement of studs, changing in tread pattern and optimizing rubber characteristics. The implementation of studs is being shied away from today. This is a result of the ever-increasing focus on air pollution and environmental hazards, caused by the studs increase in road wear. It is believed that the tread design and rubber characteristics are close to their limit of further grip improvement, and thus the industry should look in new directions. This Master’s thesis purpose replacing the conventional air-filled tires with a non-air-filled tire to improve the grip in arctic conditions. The grip obtained for tires are determined by the weight of the car and the friction between the tire and the road. The friction coefficient, used to determine friction, is a function of the contact pressure. This thesis aims to obtain a concentrated pressure on the pressure profile for the airless tire, compared to a conventional tire. A finite element analysis, using ANSYS Workbench 18.0, is performed on two distinct models. The different pressure profiles of the models are analyzed and used for discussion on whether the airless tire has the potential of increased grip, under the same loading conditions as a conventional tire.